The positron emission tomography in diagnosis of abdominal sepsis - Azevedo, Italo Medeiros; Nascimento, Rafael Pereira; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2016)
Purpose: In the perioperative phase, sepsis is associated with high morbidity and mortality and is the most important problem for the surgeon. Critically ill patients profit from an early identification and implementation of an interdisciplinary diagnostic and therapy. The purpose of this review on septic peritonitis is to give an update on the diagnosis by the use of image examination, mainly Fluor18-FDG pet scan. Methods: The literature for this review was collected with PubMed and SciElo search using the combination of “FDG,” “peritonitis” “sepsis,” and the specific terms for sepsis. Results: Rapid diagnosis for sepsis is essential for patient´s survival. A bundle of studies was performed on early recognition and on new diagnostic tools for abdominal sepsis. Although surgical intervention is considered as an essential therapeutic step in abdominal sepsis therapy, the time-point of diagnostic and source control is still controversially discussed in the literature. Conclusion: Despite many efforts, mortality of abdominal septic patients remains unacceptably high, the early diagnosis of sepsis is challenging for health care providers, and high performance methods of radiographic imaging like positron emission tomography scan can be helpful in some cases. Their diagnostic impact has to be evaluated in future studies.